Increased Systemic Immune-Inflammation Index Predicts Disease Severity and Functional Outcome in Acute Ischemic Stroke Patients - Huang, Lu (The Neurologist (Baltimore, Md.), 2023)
Systemic immune-inflammation index (SII) and system inflammation response index (SIRI) have been recently investigated as novel inflammatory and prognostic markers. Our study aimed to investigate the relationship between SII and SIRI index and severity of stroke, and to analyze the prognostic value in acute ischemic stroke (AIS) patients. The SII is defined as platelet×(neutrophil count/lymphocyte count), SIRI is defined as neutrophil count×(monocyte count/lymphocyte count). We plotted receiver operating characteristic curves of SII and SIRI for poor outcomes and calculated area under the curve (AUC) values and cutoff values. Multivariate logistic regression analysis was performed to analyze the association between SII/SIRI index and poor functional outcome. We included 234 AIS patients [mean age 69 (57-78) years; 50.4% male]. Both SII and SIRI were higher in the moderate-to-severe stroke group than in the mild stroke group [932.73 (569.84-1610.90) vs. 581.21 (386.98-1015.59), P <0.001 and 2.00 (1.24-3.13) vs. 1.35 (0.83-1.92), P <0.001]. The area under the receiver operating characteristic curve (area under the curve) value of SII (0.678, 0.608-0.748, P <0.001) tested a similar discriminatory ability compared with SIRI (0.682, 95% CI (0.612-0.751), P <0.001). Multivariate logistic regression analyses showed that SII was significantly associated with poor prognosis at discharge of AIS patients [adjusted odds ratio (95% confidence interval): 2.350 (1.149-4.803), P =0.019)], conversely, SIRI had no prognostic value. Higher SII and SIRI indexes were correlated with greater risk of stroke severity, meanwhile SII could be useful for predicting adverse clinical outcomes after AIS.